Effect of Elicitation with Iron Chelate and Sodium Metasilicate on Phenolic Compounds in Legume Sprouts - Henryk Dębski; Wiesław Wiczkowski; Marcin Horbowicz (Molecules, 2021)
Seven-day-old sprouts of fenugreek (Trigonella foenum-graecum L.), lentil (Lens culinaris L.), and alfalfa (Medicagosativa L.) were studied. The legume seeds and then sprouts were soaked each day for 30 min during 6 days with water (control) or mixture of Fe-EDTA and sodium silicate (Optysil), or sodium silicate (Na-Sil) alone. Germination and sprout growing was carried out at temperature 20 ± 2 °C in 16/8 h (day/night) conditions. Phenolic compounds (free, ester, and glycosides) content were determined by HPLC-ESI-MS/MS using a multiple reaction monitoring of selected ions. Flavonoids and phenolic acids were released from their esters after acid hydrolysis and from glycosides by alkaline hydrolysis. The presence and high content of (−)-epicatechin (EC) in fenugreek sprouts was demonstrated for the first time. Applied elicitors decreased the level of free EC in fenugreek and alfalfa sprouts but enhanced the content of its esters. Besides, elicitors decreased the content of quercetin glycosides in lentil and fenugreek sprouts but increased the content of quercetin and apigenin glycosides in alfalfa sprouts. The applied elicitors decreased the glycoside levels of most phenolic acids in lentil and p-hydroxybenzoic acid in fenugreek, while they increased the content of this acid in alfalfa. The mixture of iron chelate and sodium silicate had less effect on changes in flavonoid and phenolic acid content in legume sprouts than silicate alone. In general, the used elicitors increased the content of total phenolic compounds in fenugreek and alfalfa sprouts and decreased the content in lentil sprouts. Among the evaluated elicitors, Optysil seems to be worth recommending due to the presence of iron chelate, which can be used to enrich sprouts with this element.